PEMANFAATAN LAHAN DAN PENINGKATAN PENDAPATAN MASYARAKAT DENGAN AQUAPONIK DI JATIPULO, TANAH ABANG - Rakhdiny Sustaningrum; Rianita Pramitasari (Jurnal Kewirausahaan dan Bisnis, 2020)
DKI Jakarta residents are considered to have poverty issues and economic inequality that will affect the health and psychological problems, the Jatipulo area, is one of them. Community training activities aim to provide skills and knowledge that are expected to be capital for the application of healthy lifestyles and improve living standards. Provisioning activities and skills into an effort in the form of 1. Training in hydroponic cultivation 2. Provision of knowledge in business 3. Provision of product marketing knowledge 4. Processing post-harvest products. The activity method was finalized in a three-month presentation and field assistance method. Based on the evaluation and monitoring carried out that the hydroponic plants applied by residents and residents independently continue to make fish ponds for aquaponics, the results of which are ready for consumption and sale. Activities related to the use of simple materials in the household as hydroponic materials and the provision of capital assistance related to food for daily consumption and assistance are consistently effective in changing people's lifestyles.Keywords: aquaponic, entrepreneur, hydroponic, revenue